The ethnic identity specificity of modern Kazakhstani youth in the context of cultural globalization - Mukanova, Assel; Shormanbayeva, Dinara; Karipbayev, Baizhol; Seifullina, Galiya; Arinova, Olga (International Journal of Innovative Research and Scientific Studies, 2025)
The article examines the processes of formation, transformation, and expression of ethnic identity among contemporary Kazakhstani youth under conditions of cultural globalization and identifies the key external and internal factors that support its preservation and development. The research is grounded in a narrative approach to ethnic identity, wherein any phenomenon is conceptualized as “a story of …,” an account (not necessarily phenomenological) of a sequence of events that presupposes a particular mode of interpretation. The study finds that youth in Kazakhstan’s regional areas tend to adhere to a traditionalist model of ethnic identity with a strong emphasis on language as a primary marker whereas urban youth regard ethnic identity merely as one facet of personal identity, freely self-constructed through narrative practices. The principal conclusion is that the specificity of Kazakhstani youth ethnic identity manifests as a complex and ambiguous configuration, characterized by an underlying tension between traditionalist and modernist orientations. The practical significance of this research lies in its potential to inform the integration of case studies and project-based assignments into social studies and humanities curricula, thereby facilitating critical engagement with ethnic identity and its transformation under the influence of global trends.